ANALYSIS OF SEMIOTICS ON “PART OF ME” MUSIC VIDEO BY KATY PERRY - Irmayanti, Eka (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This research study was conducted in order to find the semiotic signs and provide explanation of the denotation, connotation and myth meanings contained in the “Part Of Me” music video by Katy Perry, which became one of her masterpieces in the music industry. As it used a self-empowerment theme, the music video contains empowering pictorial scenes and hidden meanings behind it. The music video tells a story of a woman’s struggle named Katy Perry to achieve her dream of becoming marines after an unpleasant thing happened to her love life. In the training period, she learned hard to become a strong and formidable female soldier to carry out her duties well and busy herself to be drawn from the shadows of her painful past. This research used a descriptive qualitative method in order to deliver the meanings behind each sign found in the data source. Observation method is used along with some procedures in order to collect the data. In analyzing the data, this research used semiotics theory proposed by Roland Barthes (1983). As a result of the study, this obtained 47 data of visual and verbal signs that have meanings of denotation, connotation and myth.